Daya Antioksidan Ekstrak Kulit Buah Naga Dan Sabun Ekstrak Kulit Buah Naga (Hylocereus Polyrhizuz) - Mohamad Ikram; Nining Sugihartini; Any Guntarti (Jurnal Surya Medika (JSM), 2020)
Red dragon fruit peel extract contains betalain which has antioxidant activity. In addition, this extract also contains dyes that can be used as coloring agents in cosmetic preparations. The purpose of this study was to study the activity of dragon fruit peel extract and red dragon fruit peel extract soap with various concentrations. Antioxidant activity is taken by the DPPH method. The concentration of red dragon fruit peel extract in soap is 0.3; 0.6; 0.9%. Test results show red dragon fruit extract soap has lower antioxidant activity than the extract. The increased concentration of the extract caused an increase in the antioxidant activity of the red dragon fruit peel extract soap.